2017
DOI: 10.1080/10942912.2017.1361973
|View full text |Cite
|
Sign up to set email alerts
|

Protein and lipid changes of mud shrimp (Solenocera melantho) during frozen storage: chemical properties and their prediction

Abstract: In this study, changes of protein and lipid in mud shrimp during frozen storage were investigated. Protein changes were evaluated through sulfhydryl content, disulfide bond, carbonyls, surface hydrophobicity, and intrinsic fluorescence intensity, whereas lipid oxidation was measured by free fatty acids, thiobarbituric acid reactive substances, peroxide value, and fluorescent compounds. In addition, radial basis function neural network (RBFNN) model was established to predict the quality of shrimp. Results indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 32 publications
(54 reference statements)
1
13
1
Order By: Relevance
“…The MDA and protein carbonyls value increased significantly in the tail and claw muscles during storage at +4°C and MDA reached a critical level (1 mg MDA kg −1 ) to make undesired flavours at day 12 (Jahan et al, 2004). Shi et al (2017) reported an increasing trend in the amount of TBARs and protein carbonyls during 20 weeks of storage in mud shrimp (Solenocera melantho).…”
Section: Discussionmentioning
confidence: 96%
“…The MDA and protein carbonyls value increased significantly in the tail and claw muscles during storage at +4°C and MDA reached a critical level (1 mg MDA kg −1 ) to make undesired flavours at day 12 (Jahan et al, 2004). Shi et al (2017) reported an increasing trend in the amount of TBARs and protein carbonyls during 20 weeks of storage in mud shrimp (Solenocera melantho).…”
Section: Discussionmentioning
confidence: 96%
“…Muscle protein quality can be evaluated by measuring protein composition and the biochemical properties of actomyosin (AM) . Muscle proteins can be separated into insoluble proteins (stroma), water‐soluble protein (sarcoplasmic), and salt‐soluble (myofibrillar) proteins . There is also an alkali‐soluble protein, which does not dissolve even in a high ionic solution but can be dissolved in sodium hydroxide .…”
Section: Introductionmentioning
confidence: 99%
“…POV was determined using the method of Shi et al [24] The bovine liver 0.3 g was dissolved in 9.8 ml of chloroform-methanol (7:3, v/v) and mixed for 4 s. The mixture was added with 0.05 mL of 30% ammonium thiocyanate and mixed for 4 s. Then, 0.05 m of 3.5 g/L ferrous chloride in 10 M HCl was added and mixed again for 4 s. After 5 min standing at room temperature, the absorbance was measured at 500 nm using a UV-756P spectrophotometer. The POV was expressed as milliequivalents (meq) of peroxide/kg lipid, and a reference curve was plotted using ferric chloride standard.…”
Section: Sample Processingmentioning
confidence: 99%